2020
DOI: 10.1016/j.actamat.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure and water uptake in BaLnCo2O6−δ (Ln =La, Pr, Nd, Sm, Gd, Tb and Dy)

Abstract: The structure of BaLnCo2O6-δ (Ln =La, Pr, Nd, Sm, Gd, Tb and Dy) is was studied by the means of synchrotron radiation powder X-ray diffraction, neutron powder diffraction and Transmission Electron Microscopy (TEM), while water uptake properties were analysed with the use of thermogravimetry (TG) and water adsorption isotherms. The structure refinement revealed that the dominant phase in all compositions was orthorhombic with an ordering of the A-site cations along the c-axis and ordering of oxygen vacancies al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…The orthorhombic reflections are very subtle and hard to detect using methods basing on X-ray radiation. However, in our previous study [12], we showed by the combined use of SR-XRD and neutron diffraction that BLC, BPC, and BNC adopt orthorhombic symmetry at room temperature. Therefore, even though higher symmetry refinement (P4/mmm) is possible for BNC in this study, we follow the previous refinements of higher quality data and ascribe orthorhombic structure also to BNC.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The orthorhombic reflections are very subtle and hard to detect using methods basing on X-ray radiation. However, in our previous study [12], we showed by the combined use of SR-XRD and neutron diffraction that BLC, BPC, and BNC adopt orthorhombic symmetry at room temperature. Therefore, even though higher symmetry refinement (P4/mmm) is possible for BNC in this study, we follow the previous refinements of higher quality data and ascribe orthorhombic structure also to BNC.…”
Section: Resultsmentioning
confidence: 88%
“…(Tables S1-S27). The lattice parameter doubling along the c-axis confirms A-site cation ordering, while the double b-parameter results from oxygen vacancy ordering [12]. BPC has been reported to form both tetragonal and orthorhombic structure, strongly depending on oxygen stoichiometry [4,[6][7][8]20], as well as synthesis procedure [21], but is reported to be stabilized in orthorhombic structure when oxygen non-stoichiometry (δ) is between 0.25 and 0.6 [14].…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations